Risk Management and Operational Performance of Selected Rural Banks in Laguna: Basis for Action Plan - Salvador, Philina Jean Candulisas (International Journal of Research in Interdisciplinary Studies, 2025)
This study explores the relationship between risk management practices and operational performance among selected rural banks in Laguna during the 2024–2025 academic year. Employing a descriptive-correlational research design, data were collected through self-constructed questionnaires administered to 72 managers across 18 cities and municipalities in Laguna. Statistical analyses, including weighted means and Spearman’s rho correlation, were utilized to interpret the data. Findings indicate that rural banks exhibit a moderate level of risk management, particularly in addressing employee shortages and system downtimes. Operational performance was generally assessed as good, with system downtimes managed slightly more effectively than employee shortages. A strong, positive, and statistically significant correlation was identified between risk management practices and operational performance, suggesting that effective risk management substantially contributes to enhanced operational outcomes in rural banking institutions. In response to these findings, the study proposes an action plan emphasizing cross-training programs, implementation of flexible work schedules, preventive IT maintenance strategies, and the establishment of robust communication protocols to bolster operational resilience and mitigate identified risks. The study recommends that future research extend to other regions and consider additional dimensions of risk management and operational performance within the rural banking sector.